MPPT for PV System Based on Variable Step Size Perturb and Observe Algorithm - Awang Jusoh; Rozana Alik; Tan Kar Guan; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper presents some improvements on the Perturb and Observe (P&O) method to overcome the common drawbacks of conventional P&O method. The main advantage of this modified algorithm is its simplicity with higher accuracy results, compared to the conventional methods. The operation of the entire solar Maximum Power Point Tracking (MPPT) system was observed through two different approaches, which are through MATLAB/Simulink simulation and hardware implementation. A small scale of hardware design, which consists of solar PV cell, boost converter and Arduino Mega2560 microcontroller had been utilized for further verification on the simulation results. The simulation results that was carried out by this modified P&O algorithm showed improvement and a promising performance: faster convergence speed of 0.67s, small oscillation at steady state region and promising efficiency of 95.23%. Besides, from the hardware results, the convergence time of the power curve was able to maintain at 0.2s and give almost zero oscillation during steady state. It is envisaged that the method is useful in future research of Photovoltaic (PV) system.